O ensino de frações nos anos finais do ensino fundamental - Miguel, Daniele Touza (2024)
We know how important mathematics is in our daily lives. There are several everyday situations in which we need its concepts and applications. In the student’s basic training, mathematical knowledge also becomes fundamental for their academic performance. However, as teachers and professionals in constant contact with elementary school students, we observed some important themes that are difficult for students to understand and also challenging for teachers to teach. One of these major challenges in the classroom is the teaching and learning of fractions in Elementary School, which is the school period in which students must create a stronger foundation on this content. In view of this, this work was developed through a more in-depth study of rational numbers, observing the main difficulties related to teaching and learning fractions and what the BNCC guides us on the subject, seeking an alternative that helps the teacher in the classroom. class to develop this content. Here we propose the use of some games that will support teachers in their work in the classroom.